2014
DOI: 10.4314/tjpr.v13i6.6
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective Effect of a <i>Polyopes affinis</i> (Harvey) Kawaguchi and Wang (<i>Halymeniaceae</i>)-Derived Ethanol Extract on Human Keratinocytes

et al.

Abstract: Purpose: To investigate the photoprotective effect of the ethanol extract of the red marine alga, Polyopes affinis (PAE) against ultraviolet B (UVB) radiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In general, the constituents of seaweeds can be largely divided into pigment substances, amino acids, sterols, and polyphenols. Red algae are known to contain carotenoids and chlorophyll C. Previous studies have shown the UV-protection effect of P. affinis in HaCaT cells [ 47 ], the inhibitory effect toward allergic asthma in a murine models [ 11 ], the inflammatory effect in LPS-induced RAW 264.7 cells [ 48 ], and the skin-whitening effect in B16F10 cells [ 49 ]. However, the active ingredient in P. affinis has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the constituents of seaweeds can be largely divided into pigment substances, amino acids, sterols, and polyphenols. Red algae are known to contain carotenoids and chlorophyll C. Previous studies have shown the UV-protection effect of P. affinis in HaCaT cells [ 47 ], the inhibitory effect toward allergic asthma in a murine models [ 11 ], the inflammatory effect in LPS-induced RAW 264.7 cells [ 48 ], and the skin-whitening effect in B16F10 cells [ 49 ]. However, the active ingredient in P. affinis has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated the ability of this extract to provide anti-inflammatory protection in animals using BALB/c mice (Lee et al 2013a ). A study demonstrated that Polyopes affinis (Harvey) Kawaguchi and Wang to reduce ROS, cell damage, and apoptosis induced by UVB in HaCaT cells (Hyun et al 2014 ). Another study was conducted on Polysiphonia morrowii which demonstrated to provide scavenging activity against ROS, apoptosis, and DNA fragmentation induced by UVB in HaCaT cells (Piao et al 2012 ).…”
Section: In Vitro and In Vivo Studies Based On Radiation-induced Damagementioning
confidence: 99%